The Marxism from Our Latin American Third World: : Misrepresentations and Clarifications - Henao, Hander Andrés (Disertaciones, 2024)
The Complete Edition of the Works of Marx and Engels (MEGA) has shown that the critique of political economy is a continent that is still being discovered. However, the contemporary distortions made by Edgardo Lander on this legacy have made it obsolete and meaningless for our struggles, citing an absolute knowledge of their approaches. This paper addresses the general guidelines of contemporary readings of Marxism from our Latin American third world and makes some clarifications, to then make a "record" of this tradition that returns to the foundations of its thought to the extent that it maintains a critical horizon on Modernity and capitalism. We make clear the anti-Marxist way of producing a standardization of Marx’s thought by Edgardo Lander and point in the direction of an appropriation in accordance with the anti-colonial dimension of Marx’s thought and Latin American Marxism.